Analysis of Community and Stakeholder Relationships in the Development of Cigadung Creative Tourism Urban Village - Nurhalimah, Naura Rosya; Fahrurrozi, Naufal Andyka; Hermawan, Daniel (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
This study examines local communities and stakeholders in the establishment of Cigadung Creative Tourism Urban Village in Bandung City. The success of Cigadung Creative Tourism Urban Village depends on effective cooperation between the local population, government, and tourism sector. This study uses qualitative descriptive research method included observation, interviews, and document analysis. The results demonstrated that local communities, especially Pokdarwis, are essential to tourism planning, management, and destination marketing. Government assistance and partnership with academics and businesses have helped this tourism urban community succeed. However, party coordination issues must be resolved by open communication and collaboration. This research sheds light on sustainable tourism development dynamics that can be used to benefit local welfare and culture.